2022
DOI: 10.4049/jimmunol.2100665
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Sensing by Immune Cells Occurs through Carbonic Anhydrase 2–Dependent Changes in Intracellular pH

Abstract: CO 2 , the primary gaseous product of respiration, is a major physiologic gas, the biology of which is poorly understood. Elevated CO 2 is a feature of the microenvironment in multiple inflammatory diseases that suppresses immune cell activity. However, little is known about the CO 2 -sensing mechanisms and downstream pathways involved. We found that elevated CO 2 correlates with reduced monocyte and macrophage migration in patients undergoing gastrointestinal surgery and that elevated CO 2 reduces migration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Given that monocyte infiltration, M2 macrophage polarization and hypercapnia are co-incident in COPD, our data provide novel insights into the immunometabolic landscape of hypercapnic lung disease. Hypercapnia and acidosis have previously been reported to attenuate M1 macrophage differentiation and migration, 46 which is indicative of an attenuated inflammatory immune response. Here we build on these studies to demonstrate that CO 2 per se causes a marked immunometabolic shift in monocytes and macrophages that further attenuates proinflammatory signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that monocyte infiltration, M2 macrophage polarization and hypercapnia are co-incident in COPD, our data provide novel insights into the immunometabolic landscape of hypercapnic lung disease. Hypercapnia and acidosis have previously been reported to attenuate M1 macrophage differentiation and migration, 46 which is indicative of an attenuated inflammatory immune response. Here we build on these studies to demonstrate that CO 2 per se causes a marked immunometabolic shift in monocytes and macrophages that further attenuates proinflammatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, THP‐1 cells respond to LPS 49–51 stimulation and differentiated THP‐1 macrophages have shown an altered immune response to elevated CO 2. 28,46,52 We have recently extensively characterized the shNT version of these cells described by Phelan et al 20 . where monocytes have been stably transduced with a nontarget short hairpin RNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of pneumoperitoneum requires the introduction of large amounts of CO 2 gas into the abdominal cavity, and studies have shown that CO 2 pneumoperitoneum may produce hypercapnia and have immunological effects on the body [ 24 ]. Kim I. and his colleague reported that low intra-abdominal pressure during laparoscopic colorectal surgery, which means less CO 2 , preserved innated immune homeostasis and formed a valuable addition to future enhanced recovery [ 25 ].…”
Section: Discussionmentioning
confidence: 99%